Answering the Call: Coping with DNA Damage at the Most Inopportune Time. Issue 2 (10th December 2002) - Crowley, David J.; Courcelle, Justin
Abstract : DNA damage incurred during the process of chromosomal replication has a particularly high possibility of resulting in mutagenesis or lethality for the cell. The SOS response of Escherichia coli appears to be well adapted for this particular situation and involves the coordinated up-regulation of genes whose products center upon the tasks of maintaining the integrity of the replication fork when it encounters DNA damage, delaying the replication process (a DNA damage checkpoint), repairing the DNA lesions or allowing replication to occur over these DNA lesions, and then restoring processive replication before the SOS response itself is turned off. Recent advances in the fields of genomics and biochemistry has given a much more comprehensive picture of the timing and coordination of events which allow cells to deal with potentially lethal or mutagenic DNA lesions at the time of chromosomal replication.